Control of spasticity in a multiple sclerosis model using central nervous system‐excluded CB1 cannabinoid receptor agonists. Issue 1 (11th October 2013) - Pryce, Gareth; Visintin, Cristina; Ramagopalan, Sreeram V.; Al‐Izki, Sarah; De Faveri, Lia E.; Nuamah, Rosamond A.; Mein, Charles A.; Montpetit, Alexandre; Hardcastle, Alison J.; Kooij, Gijs; de Vries, Helga E.; Amor, Sandra; et al.
Abstract : The purpose of this study was the generation of central nervous system (CNS)‐excluded cannabinoid receptor agonists to test the hypothesis that inhibition of spasticity, due to CNS autoimmunity, could be controlled by affecting neurotransmission within the periphery. Procedures included identification of chemicals and modeling to predict the mode of exclusion; induction and control of spasticity in the ABH mouse model of multiple sclerosis; conditional deletion of CB1 receptor in peripheral nerves; side‐effect profiling to demonstrate the mechanism of CNS‐exclusion via drug pumps; genome‐wide association study in N2(129×ABH) backcross to map polymorphic cannabinoid drug pump; and sequencing and detection of cannabinoid drug‐pump activity in human brain endothelial cell lines. Three drugs (CT3, SAB378 and SAD448) were identified that control spasticity via action on the peripheral nerve CB1 receptor. These were peripherally restricted via drug pumps that limit the CNS side effects (hypothermia) of cannabinoids to increase the therapeutic window. A cannabinoid drug pump is polymorphic and functionally lacking in many laboratory (C57BL/6, 129, CD‐1) mice used for transgenesis, pharmacology, and toxicology studies. This phenotype was mapped and controlled by 1–3 geneticloci. ABCC1 within a cluster showing linkage is a cannabinoid CNS‐drug pump. Global and conditional CB1 receptor‐knockout mice were used as controls. In summary, CNS‐excluded CB1 receptor agonists are a novel class of therapeutic agent for spasticity.—Pryce, G., Visintin, C., Ramagopalan, S. V., Al‐Izki, S., De Faveri, L. E., Nuamah, R. A., Mein, C. A., Montpetit, A., Hardcastle, A. J., Kooij, G., de Vries, H. E., Amor, S., Thomas, S. A., Ledent, C., Marsicano, G., Lutz, B., Thompson, A. J., Selwood, D. L., Giovannoni, G., Baker, D. Control of spasticity in a multiple sclerosis model using central nervous system‐excluded CB1 cannabinoid receptor agonists. FASEB J . 28, 117–130 (2014). www.fasebj.org